The role of solar energy usage in environmental sustainability: Fresh evidence through time-frequency analyses. (April 2023) - Kuşkaya, Sevda; Bilgili, Faik; Muğaloğlu, Erhan; Khan, Kamran; Hoque, Mohammad Enamul; Toguç, Nurhan
Abstract: The most important challenge for both developed and developing countries is to ensure sustainability while struggling with environmental degradation. CO2 emissions as a proxy for environmental degradation can be considered an obstacle to sustainability. There exist several significant works in the literature on the effects of solar energy use on environmental degradation/sustainability. In this study, the effects of the use of solar energy within different time and frequency dimensions on CO2 emissions were examined with the methodology of the continuous wavelet transform. The paper investigated the association between solar energy consumption and total energy-related CO2 emissions in the USA through Morlet wavelet analysis, which is one of the most advanced time-frequency analysis methods for the period 1990:1–2022:6. In the wavelet coherency computations, geothermal energy consumption, hydroelectric energy consumption, industrial production, and manufacturing industry production variables were also included as control variables. Empirical findings demonstrate that solar energy consumption can have reducing effects on CO2 emissions at lower frequencies (longer-term cycles) and sub-time periods (2014:1–2022:1) in the USA. The findings can guide the energy and environmental policies of developed and developing countries that aim to struggle with global warming and/or climate change through the increase in solar energy usage. Graphical abstract: Source: The graphical abstract is a slightly modified version of Bilgili et al. (2022), Fig. 2. Image 1 Highlights: Investigates the impacts of solar energy use on CO2 emissions in the USA. Follows wavelet/partial wavelet transform models. Employs the control variables of industrial production, geothermal and hydro energy, as well. The reducing effect of solar energy on CO2 emissions appears at a lower frequency. Solar energy is not effective in the reduction of CO2 emissions at higher frequencies.